Analisis Independensi dan Kecerdasan Emosional Terhadap Kinerja Audit yang Dimediasi oleh Perilaku Etis Auditor - Libriko Yodareditiyo; Endah Susilowati (BAJ: Behavioral Accounting Journal, 2022)
The performance of the auditors is currently under scrutiny from all quarters. The recent incident of the BPK auditors has caused public suspicion and doubt about the performance of the BPK. Therefore, the purpose of this study is to empirically discover and analyze the impact of independence and emotional intelligence on audit performance, which is moderated by the ethical behaviour of the pemeriksas of the Supreme Audit Office of the Republic of Indonesia (East Java Province Representative). The target population of this study is up to 165 auditors of the BPK RI representative in East Java. The sampling technique used was purposive sampling, i.e., sampling by specific criteria. Based on pre-defined criteria, the sample size was calculated so that 105 auditors were included in the study. The type of data used in the study was raw data. The data collection conducted by the researcher was done using a questionnairebased survey method. Data were processed by partial least squares (PLS) analysis using SMART PLS software. The results obtained showed that independence and emotional intelligence have a positive and significant impact on auditor ethical behaviour, while auditors’ ethical behaviour, independence and emotional intelligence have a positive and significant impact on audit performance, and auditors’ behavioural ethics as a mediating variable mediates the relationship between the variables. Thus, all the proposed hypotheses can be accepted.